Career Motivation, Distance Learning Attitude, and Time Management of the Offshore Graduate School Students of a Philippine Public University - Nollora, Apple Mhe (International Journal of Arts, Sciences and Education, 2022)
This study determined the influence of the offshore graduate school students’ career motivation and distance learning attitude on time management. Using descriptive-correlational design, the researcher conducted the study to 70 offshore graduate students enrolled in Cagayan State University (CSU), Andrews campus, Tuguegarao City, for the second semester of the Academic Year 2021-2022. The findings showed that the respondents have a high level of career motivation, specifically regarding career insight, resilience, and identity. They also manifest a favorable distance learning attitude and demonstrate a satisfactory level of time management. Significantly, the study revealed that distance learning attitude differs in terms of age. In particular, those who belong to Gen X (42-57 years old) have more favorable distance learning attitude than the Millennials (26 – 41years old) and Gen Z (10 – 25 years old. Finally, the study bared that off-shore graduate students with higher career motivation and more favorable distance learning attitude have better time management.